THE RELATIONSHIP BETWEEN THE LEVEL OF PARENTAL ATTENTION AND THE PROVISION OF TEACHER REINFORCEMENT TO THE CONFIDENCE OF GRADE IV STUDENTS OF SDN 002 IBUL - Dian Ayu Lestari; Siti Quratul Ain (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study examines the relationship between the level of parental attention and the provision of teacher reinforcement to the confidence of grade IV students of SDN 002 Ibul, Pucuk Rantau District. The correlational quantitative approach was applied with a saturated sample of 32 students. Data was collected through three sets of questionnaires that measured parental attention (15 items), teacher reinforcement (15 items), and student confidence (15 items) with a four-point Likert scale. Validity was tested using Pearson Product Moment correlation, reliability using Cronbach's Alpha, normality using Kolmogorov-Smirnov, partial hypothesis using bivariate Pearson correlation, and simultaneous hypothesis using multiple regression. All 45 instruments were declared valid (r > 0.349) and very reliable (Alpha = 0.966; 0.948; and 0.961). The normality test showed that parental attention (Sig. = 0.200) and teacher reinforcement (Sig. = 0.066) were distributed normally, while student confidence deviated from normality (Sig. = 0.013). Hypothesis testing yielded: H₀₁ rejected, meaning that there was a significant positive relationship between parental attention and student self-confidence (r = 0.772; p < 0.001); H₀₂ was rejected, meaning that there was a significant positive relationship between teacher reinforcement and student confidence (r = 0.397; p = 0.025); and H₀₃ is rejected, meaning that there is a significant simultaneous relationship of the two variables to student confidence (R² = 0.632; F = 24,882; p < 0.001), with parental attention as the dominant predictor (Beta = 0.717). These findings confirm that family involvement and strengthening practices in the classroom are important determinants of primary school students' confidence.